'Bisexual oysters': A diachronic corpus-based critical discourse analysis of bisexual representation in The Times between 1957 and 2017. Issue 2 (April 2019) - Wilkinson, Mark
Recent decades have witnessed an increase in lesbian, gay, bisexual, transgender, queer and intersex (LGBTQI) visibility in the British media. Increased representation has not been equally distributed, however, as bisexuality remains an obscured sexual identity in discourses of sexuality. Through the use of diachronic corpus-based critical discourse analysis, this study seeks to uncover how bisexual people have been represented in the British press between 1957 and 2017. By specifically focusing on the discursive construction of bisexuality in The Times, the results reveal how bisexual people are represented as existing primarily in discourses of the past or in fiction. The Times corpus also reveals significant variation in the lexical meaning of bisexual throughout the 60 years in question. These findings contribute to contemporary theories of bisexual erasure which posit that bisexual people are denied the same ontological status as monosexual identities, that is, homosexuality and heterosexuality.